2017
DOI: 10.15277/bjd.2017.140
|View full text |Cite
|
Sign up to set email alerts
|

T1resources.uk; rated, reviewed, reliable. A co-created website for people affected by type 1 diabetes.

Abstract: People with type 1 diabetes (T1DM) spend many hours each year on self-care activities. They are often isolated and find it difficult to access trustworthy information online. T1resources.uk fills this gap: it is the first of its kind to provide a curated library of resources created for and by people with T1DM. The website is co-curated, with equal healthcare professional and peer representation and input. It signposts its users to pre-existing digital material, having first ensured their safety and usability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Of the 96 publications included in the scoping review,11 13 publications (14%) contained no information that was relevant to the objectives of this study and were therefore excluded. Thus, our analysis included 83 publications, reporting on 21 patient-driven innovations 18–100. The publications that were excluded concerned the two innovations ( DIY-APS 101–107 and PatientsLikeMe 108–113) that accounted for most of the publications included (n=49, 59%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 96 publications included in the scoping review,11 13 publications (14%) contained no information that was relevant to the objectives of this study and were therefore excluded. Thus, our analysis included 83 publications, reporting on 21 patient-driven innovations 18–100. The publications that were excluded concerned the two innovations ( DIY-APS 101–107 and PatientsLikeMe 108–113) that accounted for most of the publications included (n=49, 59%).…”
Section: Resultsmentioning
confidence: 99%
“…One way to enhance patient agency in self-care was through the curation of trustworthy information and knowledge. Innovations included shared libraries of quality-assured diagnosis-specific self-care information ( T1resources.uk ), as well as personal health records (eg, MediStori), and online health information platforms (eg, PatientsLikeMe ) that provided functionalities for collecting, presenting, and comparing personal health data over time, and with others 64 72 83 99. These platforms contributed to patient agency in self-care by providing patients with tools to initiate self-monitoring and engaging in self-experimentation, possibly inspired by experiences of other platform users.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 20 identified innovations addressed the unmet needs of patients and family caregivers with diabetes (7 innovations, 46 publications18–63); cancer (1 innovation, 1 publication64); rare diseases (3 innovations, 5 publications65–69); gastrointestinal diseases (2 innovations, 4 publications70–73); disabilities (2 innovations, 3 publications74–76); Parkinson’s disease (2 innovations, 3 publications77–79) and mental illness (1 innovation, 2 publications80 81). There were also innovations targeting unmet needs of multiple conditions (2 innovations, 32 publications82–113).…”
Section: Resultsmentioning
confidence: 99%
“…Although studies have suggested that education is an important aspect to improve existing mHealth apps in diabetes management, this has only been adopted by a few apps [ 15 , 47 ]. As the educational component was provided primarily in the nutritional values displayed in user-posted recipes, it is recommended to modify the web-based platform, which could be cocreated by people with diabetes and health care professionals, thereby using existing learning resources on diabetes management and minimizing costs [ 53 ].…”
Section: Discussionmentioning
confidence: 99%